Effect of middle-age plasma therapy on ileum morphology, immune defense (IgA) and cell proliferation (Ki-67) of female aged rats - Asmaz, Ender Deniz; Teker, Hikmet Taner; Sertkaya, Zeynep Tuğçe; Ceylani, Taha; Genç, Aysun İnan (Springer Science and Business Media LLC, 2024)
Blood plasma therapy, a new treatment method to eliminate the damage and deterioration caused by aging in many organ systems, has attracted increasing attention. The digestive tract, which cooperates with many different systems, has strong effects on our health. In the present study, the effects of plasma therapy on the ileum of elderly rats were investigated. Wistar rats (n = 7; 12-15 months old) were given pooled plasma collected from middle-age rats (6 months, n =28) (for 30 days, 0.3 ml daily, intravenously into the tail vein). At the end of the experiment, villus height, crypt depth, total mucosal thickness and surface absorption area were evaluated. In addition, the effects of IgA, which plays a role in the digestive system's defense against microorganisms, were examined. Both the cell proliferation intensity and proliferation index were evaluated in crypt cells. An increase was determined in all morphological parameters in the experimental group. Similarly, plasma application decreased IgA expression and numbers in the experimental groups. Contrarily, cell proliferation parameters showed a significant increase in the experimental groups' crypt cells. Therefore, we found that the treatment supports the digestive system in terms of both nutrient utilization and absorption-related parameters and has a protective effect on intestinal immune system parameters.
Keywords: Aging; Ki-67 Antigen; Ileum; Ki-67; Animals; Female; Wistar rat; Rats, Wistar; Blood plasma treatment; IgA; Rats; Immunoglobulin A; Cell Proliferation